Betacyanins extraction from Hylocereus polyrhizus using alcohol/salt-based liquid biphasic partitioning system and antioxidant activity evaluation. Issue 5 (24th March 2019) - Leong, Hui Yi; Ooi, Chien Wei; Law, Chung Lim; Julkifle, Advina Lizah; Show, Pau Loke
ABSTRACT: Betacyanins have gained increasing interest as natural food dye because of their health-promoting effects. This study investigated the betacyanins extraction from peel and flesh of red–purple pitaya using ethanol/K2 HPO4 -based liquid biphasic partitioning system (LBPS) by optimised concentrations of ethanol, K2 HPO4, NaCl and crude. Overall, the highest values of betacyanins concentration in alcohol-rich top phase (C t ), phase volume ratio (V r ) and partition coefficient (K) of betacyanins that represented an optimum betacyanins extraction from the peel (98.080%, 1.667 and 51.097, respectively) and flesh (96.256%, 2.167 and 25.764, respectively) were achieved. Lastly, conventional solvent extractions, colour characterisation and antioxidant activity evaluation were conducted.